Variations in cochlea shape reveal different evolutionary adaptations in primates and rodents - Joaquin del Rio; Roxana Taszus; Manuela Nowotny; Alexander Stoessel (Scientific Reports, 2023)
Abstract The presence of a coiled cochlea is a unique feature of the therian inner ear. While some aspects of the cochlea are already known to affect hearing capacities, the full extent of the relationships between the morphology and function of this organ are not yet understood—especially when the effect of body size differences between species is minimized. Here, focusing on Euarchontoglires, we explore cochlear morphology of 33 species of therian mammals with a restricted body size range. Using μCT scans, 3D models and 3D geometric morphometrics, we obtained shape information of the cochlea and used it to build phylogenetically corrected least square models with 12 hearing variables obtained from the literature. Our results reveal that different taxonomic groups differ significantly in cochlea shape. We further show that these shape differences are related to differences in hearing capacities between these groups, despite of similar cochlear lengths. Most strikingly, rodents with good low-frequency hearing display “tower-shaped” cochleae, achieved by increasing the degree of coiling of their cochlea. In contrast, primates present relatively wider cochleae and relative better high frequency hearing. These results suggest that primates and rodents increased their cochlea lengths through different morpho-evolutionary trajectories.